Menilai Dampak Ganda Harga Kopi dan Nilai Tukar terhadap Nilai Ekspor Kopi Indonesia - Azhari, Azhari; Konadi, Win; Musrizal, Musrizal (Jurnal Cita Ekonomika, 2025)
Indonesia, as one of the largest coffee-producing countries in the world, faces challenges in managing coffee exports which are affected by fluctuations in global coffee prices and the rupiah exchange rate. This study aims to analyze the simultaneous impact of coffee prices and exchange rates on the value of Indonesian coffee exports. Using the Autoregressive Distributed Lag (ARDL) method, this study explores the short-term and long-term relationship between coffee prices, exchange rates, and Indonesian coffee exports from 2001 to 2023. The results show that coffee prices and exchange rates have a significant influence on Indonesia's coffee exports, with a long-term relationship that shows that rupiah depreciation and higher coffee prices increase export value. These findings highlight the importance of policies that support coffee price and exchange rate stabilization to increase the competitiveness of coffee exports. This can be done by improving the quality of coffee beans and increasing the resources of coffee farmers in Indonesia. For further research, it is recommended to integrate more non-price factors, such as branding, the role of certification bodies, social and cultural factors that can affect the global market demand for coffee.